Saudi Students Who Are Deaf and Hard of Hearing in a US University: A Qualitative Case Study - د. عبدالعزيز القحطاني (مجلة العلوم التربوية والنفسية, 2025)
The current study investigated the experience of Saudi students who are deaf and hard of hearing (DHH) and were studying at the college level in a U.S. university. The investigation employed a qualitative case study approach, closely aligning with the study's requirements. Relevant data was collected through a semi-structured interview. The interviews were conducted by four DHH students. The results revealed a misunderstanding of deaf minority students’ culture and communication modes at the college level. Additionally, this leads to the creation of gaps in interaction between international and non-international students. This study suggests the importance of early proactive programs on school campuses that assist students in making new friends and sharing experiences and cultures. Keywords: college, deaf, hard of hearing, international student, university.